2017
DOI: 10.1063/1.4989851
|View full text |Cite
|
Sign up to set email alerts
|

Uniform large-area growth of nanotemplated high-quality monolayer MoS2

Abstract: Over the past decade, it has become apparent that the extreme sensitivity of 2D crystals to surface interactions presents a unique opportunity to tune material properties through surface functionalization and the mechanical assembly of 2D heterostructures. However, this opportunity carries with it a concurrent challenge: an enhanced sensitivity to surface contamination introduced by standard patterning techniques that is exacerbated by the difficulty in cleaning these atomically thin materials. Here, we report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 62 publications
0
7
1
Order By: Relevance
“…Since the FWHM of the E 2g 1 mode is known to be relatively insensitive to the number of layers, it could be used as an index for comparing the crystalline quality. The FWHM values of E 2g 1 and A 1g of our film are found to be 3.0 and 3.2, respectively (Figure S3), which are narrower than previously reported values taken from TVS-grown films. Furthermore, single-layer MoS 2 films grown by CVD have exhibited the values in the range of 3.2–3.8 for E 2g 1 and 3.7–6.8 cm –1 for A 1g , suggesting that the crystalline quality of our TVS-grown film is comparable to that of the CVD-grown films in the previous reports. The chemical composition of the MoS 2 film was characterized by XPS (see Figure S4).…”
Section: Resultscontrasting
confidence: 52%
“…Since the FWHM of the E 2g 1 mode is known to be relatively insensitive to the number of layers, it could be used as an index for comparing the crystalline quality. The FWHM values of E 2g 1 and A 1g of our film are found to be 3.0 and 3.2, respectively (Figure S3), which are narrower than previously reported values taken from TVS-grown films. Furthermore, single-layer MoS 2 films grown by CVD have exhibited the values in the range of 3.2–3.8 for E 2g 1 and 3.7–6.8 cm –1 for A 1g , suggesting that the crystalline quality of our TVS-grown film is comparable to that of the CVD-grown films in the previous reports. The chemical composition of the MoS 2 film was characterized by XPS (see Figure S4).…”
Section: Resultscontrasting
confidence: 52%
“…We envisage that the thin-film sulfurization approach can similarly provide a versatile method of synthesizing a broad range of TMDs, heterostructures or alloys based on the choice of precursors 30 . This approach may also lend itself to TMD nanostructure fabrication by pre-patterning the metal oxide precursor prior to sulfurization 60 .…”
Section: -59mentioning
confidence: 99%
“…Recently it was demonstrated that the crystallinity in the MoS 2 layers is dependent on the deposition temperature and thickness of the metallic Mo film [14]. These technological variables were also found acceptable to tune the properties layer by layer in the stacked MoS 2 structures [15]. However, there are still no clear guiding principles acceptable to relate the technological conditions and the resulting properties of the 2D TMDs based structures.…”
Section: Introductionmentioning
confidence: 99%